Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4995/riai.2018.9233
|View full text |Cite
|
Sign up to set email alerts
|

Apoyo a la toma de decisión en una red de evaporadores industriales

Abstract: <p>La planificación de la producción y tareas de mantenimiento en una red de  equipos es una tarea cuya complejidad aumenta exponencialmente con el número de productos, equipos y tareas. Encontrar soluciones óptimas económicas o de eficiencia de recursos) se hace especialmente difícil para un planificador humano, más aún cuando se requiere tomar decisiones en breves periodos de tiempo. Este trabajo aborda el problema de distribución de carga en tiempo real y programación de limpiezas en una red de evapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…1), which also affects the overall specific steam consumption. Fouling in the heating line is out of this work, for details on how to deal with it see [8].…”
Section: A Outlet Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…1), which also affects the overall specific steam consumption. Fouling in the heating line is out of this work, for details on how to deal with it see [8].…”
Section: A Outlet Temperaturementioning
confidence: 99%
“…The complete evaporation system in Lenzing A.G. can be mainly described by two networks of equipment. The first one concerns the evaporation plants where decisions on load allocation need to be taken [8]. The second one refers to the cooling systems attached to each plant, feed by a water distribution network, where decisions on water flows to plants need to be taken, i.e the problem addressed in this work.…”
Section: Further Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, many people in the process control community have been devoting efforts during the last decade to develop efficient and reliable models to support operators and managers in their decisions [9,10]. The preferred option is building models that combine as much physical information as possible/acceptable with relationships obtained from experimental data collected from the plant [11].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the absolute steam consumption (ASC) in each plant is computed by ASC = SSC • EC. Plant surrogate models were developed to estimate the SSC in Kalliski et al (2019), which, after straightforward manipulations, is found to depend on EC and on the cooling capacity of the surface condenser C pow , as shown in (1). The cooling system performance is also modelled experimentally: the outlet cooling-water temperature of the condensers T out is estimated by a polynomial function up to degree 3 on the cooling-water flow F w and affine in its inlet temperature T in , as proposed in (Marcos et al, 2018):…”
mentioning
confidence: 99%